Enhancing Discipline and Reducing Employee Turnover Through PKWT Implementation and Digital Attendance - Ellen Wu; Agustinus Setyawan (Sean Institute, 2026)
This study focuses on improving employee discipline and reducing turnover at Toko Citra, a retail MSME in Batam, through the implementation of Fixed-Term Employment Agreements (PKWT) and a digital attendance system. Prior to this project, Toko Citra faced several human resource management issues, including frequent employee turnover due to the absence of formal employment contracts and weak discipline control caused by a manual attendance system. These conditions made workforce management inefficient and disrupted daily operations. Data was collected through direct observation, interviews with the business owner, and documentation during the internship period. Based on the identified problems, PKWT documents were prepared for all employees in accordance with applicable labor regulations, and a digital attendance system using the Gajihub application was implemented. Employees were registered, introduced to the system, and assisted during the initial implementation stage. The results show that employee administration has become more structured and transparent. All employees are now officially bound by PKWT contracts, while the digital attendance system enables real-time monitoring and improves discipline. In the first month, employee attendance reached 87%, indicating positive changes in work discipline. Overall, the implementation of PKWT and digital attendance systems contributed to better workforce stability and supported the operational sustainability of Toko Citra.